Monetary policy under the international gold standard, 1880-1914 - Bloomfield, Arthur I. (New York : Federal Reserve Bank, 1959)
This book examines the functioning of the pre-1914 gold standard. The book was sponsored through the grant from the Rockefeller Foundation.
Reprint of the 1959 ed. published by the Federal Reserve Bank of New York.
Includes bibliographical references.
usc 18/09/18
Loans
Keywords: Monetary policy; Banks and banking, Central; Gold standard